Weak founder effects but significant spatial genetic imprint of recent contraction and expansion of European beech populations - Lander, TA; Klein, EK; Roig, A; Oddou-Muratorio, S (Springer Nature, 2020)
Understanding the ecological and evolutionary processes occurring during species range shifts is important in the current context of global change. Here, we investigate the interplay between recent expansion, gene flow and genetic drift, and their consequences for genetic diversity and structure at landscape and local scales in European beech (Fagus sylvatica L.) On Mont Ventoux, South-Eastern France, we located beech forest refugia at the time of the most recent population minimum, ~150 years ago, and sampled 71 populations (2042 trees) in both refugia and expanding populations over an area of 15,000 ha. We inferred patterns of gene flow and genetic structure using 12 microsatellite markers. We identified six plots as originating from planting, rather than natural establishment, mostly from local genetic material. Comparing genetic diversity and structure in refugia versus recent populations did not support the existence of founder effects: heterozygosity (He = 0.667) and allelic richness (Ar = 4.298) were similar, and FST was low (0.031 overall). Still, significant spatial evidence of colonization was detected, with He increasing along the expansion front, while genetic differentiation from the entire pool (βWT) decreased. Isolation by distance was found in refugia but not in recently expanding populations. Our study indicates that beech capacities for colonization and gene flow were sufficient to preserve genetic diversity despite recent forest contraction and expansion. Because beech has long distance pollen and seed dispersal, these results illustrate a 'best case scenario' for the maintenance of high genetic diversity and adaptive potential under climate-change-related range change.